CABARAN PENGAPLIKASIAN JANJI (WA’D) DALAM KONTRAK PERBANKAN ISLAM DI MALAYSIA: The Challenges of Application of Promise (Wa’d) in Islamic Banking Contracts in Malaysia - Yaakub, Fadziani; Buang, Ahmad Hidayat (Jurnal Syariah, 2019)
The concept of promise in Islamic banking contracts in Malaysia was introduced around in 2005. Its application is still a polemic among critics although the principle was recognized by Shariah Advisory Council of Bank Negara Malaysia (SAC BNM) in its 157th meeting on 31st March 2015. This polemic has an impact on the mechanism and validity of Islamic banking contracts such as Murabahah to Purchase Order (MPO), al-Ijarah Thumma al-bay’ (AITAB) and Musharakah Mutanaqisah (MM) which make the contracts controversial. Using the data collected from library research and interviews, this article attempts to analyze the subject qualitatively in order to identify the challenges and obstacles faced by the industry in the application of such principle. The important finding from this study shows that the issue on the application of the principle resulted from the perceptions among the community and industrial players towards the resolutions by SAC BNM, the inability of the lawyers and consumers to fully understand the concept of promise, lack of courage among industrial players to innovate new products based on promise, the obstacles from shariah committee Islamic banking itself, and its application is limited to those who accept the binding promise.